Zróżnicowanie cen wybranych produktów spożywczych w sieciach handlowych i małych sklepach osiedlowych - Wyszkowska, Zofia (Prices Differentation of Chosen Groceries in Market Chains and in Small District Grocery Stores, 2005)
The aim of this work is to get to know the prices differentation of groceries in market chains and in small district grocery stores. Fifteen groceries were analyzed. The changes of prices were observed in seven markets or grocery stores for the same products for 40 weeks. In the article the changes of bread, rolls and croissants prices are included. The hypotesis saying that together with the growth of selling area markets have lower prices has not been proved.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 434-439